2020
DOI: 10.3746/pnf.2020.25.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Phenolic Content, Antioxidant and Antimicrobial Activities of Oil and Non-Oil Extracts of Citrus sinensis (L.) Osbeck Seeds

Abstract: The seeds of Citrus sinensis (L.) Osbeck (sweet orange) are waste products usually discarded. They may however contain phytochemicals that have potent bioactivities. In this study, the phenolic content, and antioxidant and antimicrobial activities of oil and non-oil (solid) extracts of C. sinensis seeds were evaluated using standard protocols. The seed oil contained significantly ( P >0.05) higher contents of total phenol and total flavonoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Discarded seeds of Hamlin, Natal, Perario and Valencia orange varieties are promising sources of essential oils, and their chemical composition accounts for a high content of carotenoids, phenolic compounds, tocopherols, and phytosterols, which play a relevant role in the free radical scavenging capacity of this by-product [ 62 ]. Moreover, it was demonstrated that orange seed oil and non-oil extracts possess interesting antibacterial and antifungal properties, other than antioxidant, helpful for the development of antimicrobial agents [ 63 ].…”
Section: Citrus Sinensis (L) Osbeckmentioning
confidence: 99%
“…Discarded seeds of Hamlin, Natal, Perario and Valencia orange varieties are promising sources of essential oils, and their chemical composition accounts for a high content of carotenoids, phenolic compounds, tocopherols, and phytosterols, which play a relevant role in the free radical scavenging capacity of this by-product [ 62 ]. Moreover, it was demonstrated that orange seed oil and non-oil extracts possess interesting antibacterial and antifungal properties, other than antioxidant, helpful for the development of antimicrobial agents [ 63 ].…”
Section: Citrus Sinensis (L) Osbeckmentioning
confidence: 99%
“…Total flavonoid contents were estimated using the method described by other authors [ 63 , 64 ]. The extract (0.5 mL of 1 mg/mL) was mixed with 1.5 mL of methanol.…”
Section: Methodsmentioning
confidence: 99%
“…: grzybów Aspergillus [15,16], Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, Bacillus subtilis, Listaria monocytogenes czy Salmonella sp. [17,18].…”
Section: Wstępmentioning
confidence: 99%